The m5C reader Ybx1 regulates embryonic cortical neurogenesis by promoting progenitor cell cycle progression. - Jian Zhang; Pengfei Che; Zhuoxuan Yang; Pingrui Zhang; Yuxuan Shui; Xibin Lu; Jiuzhou Xu; Yuanchu She; Yanbo Zhang; Jun Yu; Sheng-Jian Ji (PLoS Biology)
The reversible epitranscriptomic mark, 5-methylcytosine (m5C) modification, is implicated in numerous cellular processes, but its role in neural development remains largely unexplored. In this study, we discovered high expression of the m5C reader Ybx1 in the developing mouse cortex. To elucidate its role in cortical development, Ybx1 was ablated in embryonic cortical neural stem cells (NSCs). Interestingly, conditional knockout (cKO) of Ybx1 led to perinatal mortality in mice, along with abnormal cortical development. Cortical progenitor cells lacking Ybx1 exhibited impaired proliferation and differentiation. Multi-omics analysis identified the target mRNAs of Ybx1, which encode the key cell cycle regulatory proteins converging on cyclin D2 (Ccnd2). Ybx1 was found to regulate the stability of its target transcripts. Both knockdown and overexpression of Ybx1 targets via in utero electroporation confirmed that they mediated Ybx1 regulation of proliferation and differentiation of neural precursor cells. Further analysis showed that the G1 to S phase transition in cortical progenitor cells is delayed in the Ybx1 cKO. This study highlights the crucial function of the m5C reader protein Ybx1 in promoting cell cycle progression of the embryonic cortical progenitors, essential for proper cortical development.